AI Users Are Not All Alike: The Characteristics of French Firms Buying and Developing AI - Flavio Calvino; Luca Fontanelli (CESifo GmbH, 2024)
In this work we characterise French firms using artificial intelligence (AI) and explore the link between AI use and productivity. We distinguish AI users that source AI from external providers (AI buyers) from those developing their own AI systems (AI developers). AI buyers tend to be larger than other firms, but this relation is explained by ICT-related variables. Conversely, AI developers are larger and younger beyond ICT. Other digital technologies, digital skills and infrastructure play a key role for AI use, with AI developers leveraging more specialised ICT human capital than AI buyers. Overall, AI users tend to be more productive, however this is related to the self-selection of more productive and digital-intensive firms into AI use. This is not the case for AI developers, for which the positive link between AI use and productivity remains evident beyond selection.
Keywords: D20; J24; O14; O33; 330; technology diffusion; artificial intelligence; digitalisation; productivity